Heiddegerian enframing, nihilism & affectlessness in J.G. Ballard’s Crash - Sánchez Fernández, Carlos (International Journal of English Studies, 2019)
J.G. Ballard’s novel Crash (1973) allows a reading in the terms of Heidegger’s concept of Ge-stell or enframing, according to which in modernity everything, humans included, is seen as a mere means to often questionable ends. Prompted by violent sexual fantasies and an unleashed death drive, its main characters, a wild bunch of symphorophiliac drivers, live a life of existential nihilism, treating human beings as objects, mere fodder for their prearranged car crashes. In so doing, they take an active part in a general process of dehumanisation afflicting Western civilisation, where people are just standing reserve (Bestand). This would be closely linked to so-called affectlessness, where emotions go nowhere but to an ever-increasing self-absorption in a world without others. In turn, this would be symptomatic of a civilisational shift from word to image, in a society where technology and performativity reign supreme and everything is evacuated of meaning.